ANALISA PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PERUMAHAN PINANG JAYA PALEMBANG - Andini Utari Putri; Puspa Djuita (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
Increasing business competition in the housing sector has led companies to adopt appropriate marketing strategies so that their businesses can survive and win the competition. This study aims to determine the effect of pricing on consumer purchasing decisions in Palembang Pinang Jaya Housing. This type of research is quantitative with a descriptive approach that is by describing and describing the variables studied and then drawn conclusions. The object of research that becomes the independent variable is the price (X1) and the purchase decision (Y) as the dependent variable. The population in this study were 35 customers in Palembang Pinang Jaya Housing. Sampling in this study uses a saturated sample technique so that the entire population is taken to be the research sample. The instrument test was carried out with the validity and reliability test, the normality test, the hypothesis test and the analysis technique used was a simple regression analysis. The results showed that the price had a significant effect on purchasing decisions at Pinang Jaya Palembang Housing. This can be seen from the research that has been investigated by researchers that shows from the t test results obtained tcount> ttable (1,402> 0.05) then H0 is rejected. meaning that the price has a significant effect on purchasing decisions. Based on the significance value: from the Coefficients table obtained significance of 0.170> 0.05, so it can be concluded that the variable Price (X) influences the purchase decision variable (Y).